A Computational Mechatronics Approach for the Analysis, Synthesis and Design of a Simple Active Biped Robot: Theory and Experiments - L.-I. Lugo-Villeda; V. Parra-Vega (Applied Bionics and Biomechanics)
Biped walking is a quite complex process that has been mastered only by human beings. Transferring this skill to a robot requires implementing advanced techniques in every aspect. To this end, a computational mechatronics platform was integrated to run the scheme for the analysis, synthesis and design to achieve planar biped walking. The result is an advanced computational tool that integrates advanced modeling and control as well as path planning techniques along with hardware-in-the-loop for perhaps the simplest biped robot. An experimental underactuated three-degree-of-freedom (two active and one passive) active biped robot yields encouraging results; that is, achieving biped walking with this simple device requires adding a telescopic support leg. Considering a more complete dynamic model to take into account frictional and contact forces.